Hubungan Antara Kualitas Tidur Dengan Frekuensi Kejang Pada Pasien Epilepsi Di RSUD Dr. Moewardi Surakarta - Nisa, Resky Aulia; , dr. Ani Rusnani Fibriani, Sp.S; , dr. Budi Hernawan (2015)
Background: Epilepsy be familiar since era-19. Yet a comprehension of this disease is less till a accusative of disease epilepsy un diagnose and don‟t get a good service with. Epilepsy can be found in all age and can induce a mortality the most humanly found in develop state be compared in progressive state caused by various factors as the risk of disorders of the central nervous infection, other factor that may influence the occurrence of seizures associated with sleep is sleep deprivation. Sleep is one of the basic human needs that must be met for body recovery process. Sleep quality is the ability of a person to be able to maintain in order to stay asleep, getting a sufficient amount of sleep and asleep in his sleep. Patients with epilepsy is linked to sleep likewise in contrast sleep can affect the onset in patients with epilepsy. So there is a reciprocal relationship between the two and impact on quality of life of people with epilepsy. Purpose: Explained relationship between sleep quality with frequency of seizures in patient with epilepsy in RSUD Dr. Moewardi Surakarta. Method: Observational study of cross sectional analytic approach 44 patients, consisted of 22 patients with good quality of sleep and 22 patients with bad quality of sleep. Sampling use non random sampling. Result: Data analysis used chi square test be found value p: 0,003 (p<0,05) from result of quality of sleep and frequency stiff. Conclusion: based on result of research that have done bad quality impact 10x influence frequency stiff to patient of epilepsy. Result chi square test be found value p: 0,003 be of sleep and frequency of stiff to patient epilepsy in RSUD Dr. Moewardi Surakarta.